2011
DOI: 10.1007/s00421-011-2016-y
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation in the ocular and cerebral arteries during the cold pressor test and handgrip exercise

Abstract: The aim of this study was to determine whether autoregulation exerts similar effects in the ocular and cerebral vessels, which are both branches of the internal carotid artery. Ocular blood flow velocities, cerebral blood flow velocity and blood pressure were measured in 11 subjects during a 2-min resting period, static handgrip exercise (HG) and a cold pressor test (CPT). Blood velocity data for the superior and inferior temporal retinal arterioles (STRA and ITRA, respectively) and the retinal and choroidal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…No change was reported in retinal blood flow despite an increase in MAP during a cold pressor test, whereas choroidal blood flow increased 19) . Choroidal blood flow increased with an increase in MAP during dynamic exercise, while retinal blood flow remained at resting baseline level 12) .…”
Section: Limited Effects Of Autoregulation On Ocular Circulationmentioning
confidence: 77%
See 2 more Smart Citations
“…No change was reported in retinal blood flow despite an increase in MAP during a cold pressor test, whereas choroidal blood flow increased 19) . Choroidal blood flow increased with an increase in MAP during dynamic exercise, while retinal blood flow remained at resting baseline level 12) .…”
Section: Limited Effects Of Autoregulation On Ocular Circulationmentioning
confidence: 77%
“…The authors, in turn, observed that an increase in choroidal blood flow occurred concomitantly with an increase in MAP by roughly 15% during handgrip exercise (Fig. 4) 19) . These inconsistent results can be due to different types of exercise.…”
Section: Inner Ocular Blood Flow During Static Exercisementioning
confidence: 90%
See 1 more Smart Citation
“…Laser-speckle images were obtained using a laser-speckle flowgraphy (LSFG) system (SoftCare, Fukuoka, Japan), which is described elsewhere (for example, [8]). The LSFG measurements were made in triplicate at each time point and the mean of the three values was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, whether autoregulation exists in the human retina has yet to be established. One study found no change in the retinal circulation during either the cold pressor test or handgrip exercise, indirectly suggesting the existence of autoregulation 48) . Consistent with the presence of autoregulation, choroidal flow did not change during submaximal dynamic exercise even where there was a pressor response 45,46) .…”
Section: Ocular Flow During Exercisementioning
confidence: 99%